2017
DOI: 10.18488/journal.8.2017.52.194.207
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stock Market Development on Economic Growth in OPEC Countries: Does Oil Price Movement Matter? Fresh Evidence from Nigeria

Abstract: Article HistoryThis study investigates the relationship link crude oil price and stock market development and economic growth in one of the OPEC countries with emphasis on Nigeria over the period 1981 to 2014, using the latest methodology autoregressive distributed lag approach (ARDL) to cointegration analysis. Three indicator of stock market development are constructed using principal component analysis. The revels the dominant role of rule oil price as one of the engine for economic growth in Nigeria. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Several studies have examined the connections between oil prices and stock market movements in oil-exporting countries. For example, Okere and Ndubuisi (2017) have investigated the effects of oil price shocks on the Nigerian economy. The results reveal that crude prices significantly influence the economy by directly impacting the stock market's performance.…”
Section: Oil Exportersmentioning
confidence: 99%
“…Several studies have examined the connections between oil prices and stock market movements in oil-exporting countries. For example, Okere and Ndubuisi (2017) have investigated the effects of oil price shocks on the Nigerian economy. The results reveal that crude prices significantly influence the economy by directly impacting the stock market's performance.…”
Section: Oil Exportersmentioning
confidence: 99%
“…They concluded that financial measures do in fact mitigate the effects of oil price volatility, and the introduction of these measures can reduce or completely eliminate the negative effects of oil price volatility on growth. Okere and Ndubuisi (2017) also investigated the relationship between crude oil price and stock market development and economic growth in Nigeria between 1981 and 2014 using the ARDL model. The study concluded that the dominant role of oil price is one of the engines driving economic growth in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This motivated me to offer a recent and a comprehensive study. Generally speaking, studies forwarded towards the relationship between financial development and economic expansion, concluded that, this correlation is different in comparison with developed economies because of the dominance of the oil sector on economic activities (Samargandi et al, 2014;Quixina & Almeida, 2014;Bakwena & Bodmanm, 2011;Cevik & Rahmani, 2013;Nwani et al, 2016;Okene & Ndubuisi, 2017;Nwamuo, 2018). This work introduces the need to present a recent study that considers the main factors of capital market which expected to affect economic growth.…”
Section: Introductionmentioning
confidence: 99%